2016
DOI: 10.1097/ccm.0000000000001384
|View full text |Cite
|
Sign up to set email alerts
|

A Donation After Circulatory Death Program Has the Potential to Increase the Number of Donors After Brain Death*

Abstract: The development of a national donation after circulatory death program has had minimal impact on the number of donation after brain death donors. The number of donation after brain death donors could increase with changes in end-of-life care practices to allow the evolution of brain death and increasing the availability of ancillary testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…In the early days of the program, patient and graft outcomes were inferior to recipients of DCD livers, but with increasing experience and improved techniques this difference is decreasing. The DCD program was developed to ensure that the organ donation and transplantation occurs whenever appropriate, but a prospective audit showed no evidence that the presence of an active DCD program results in a switch of donors from DBD to DCD …”
Section: Challengesmentioning
confidence: 99%
See 3 more Smart Citations
“…In the early days of the program, patient and graft outcomes were inferior to recipients of DCD livers, but with increasing experience and improved techniques this difference is decreasing. The DCD program was developed to ensure that the organ donation and transplantation occurs whenever appropriate, but a prospective audit showed no evidence that the presence of an active DCD program results in a switch of donors from DBD to DCD …”
Section: Challengesmentioning
confidence: 99%
“…Measures adopted to improve consent rates include changing public behavior to support organ donation, removing actual or perceived objections to donation, and ensuring that every potential donor is identified and that the family is approached by personnel who are trained to seek consent whenever appropriate. The lack of intensive therapy unit (ITU) beds remains an issue: for example, a study in 2010 showed the United Kingdom has 3 ITU beds per 100,000 population compared with 25 beds per 100,000 population in Germany . The shortage of beds has significant implications on donation because this may affect how end‐of‐life care is administered.…”
Section: Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Of those 257, 134 proceeded as an organ donor. "A donation after circulatory death program has the potential to increase the number of donors after brain death" may be a somewhat misleading title to the study by Broderick et al (4). Perhaps the most important question, these researchers asked in this study was whether any of the DCD donors could have become DBD donors.…”
mentioning
confidence: 89%